Synthesis of a series of benzothiazole amide derivatives and their biological evaluation as potent hemostatic agents. Issue 12 (7th February 2018) - Nong, Wenqian; Zhao, Anran; Wei, Jinrui; Cheng, Hui; Luo, Xuan; Lin, Cuiwu
Abstract : New benzothiazole amide derivativeQ2 is a potential hemostatic drug molecule with good hemostatic activity. Abstract : A series of benzothiazole amide derivatives were synthesized through a facile and efficient method via a nucleophilic acyl substitution reaction between 2-aminobenzothiazole and various cinnamic acid compounds. The obtained products exhibited good thermal stabilities. All compounds were evaluated for their in vitro hemostatic activities using the commercially available standard drug etamsylate as a positive control. The results showed that compoundQ2 had a significant partial coagulation activity, reduced capillary permeability at 5, 10 and 50 μmol L −1, activated thrombin activity, and a more potent platelet aggregation activity than the positive control group (etamsylate, up to 1283.9 times in the nanomole range). A molecular modeling study revealed that compoundQ2 was a competitive thrombin activator. Therefore, Q2 may be a potential lead for further biological screening and for the generation of drug molecules. Moreover, the structure–activity relationship of the prepared compounds is also discussed herein.